2004
DOI: 10.1037/0012-1649.40.2.140
|View full text |Cite
|
Sign up to set email alerts
|

Infants of Chronically Depressed Mothers Learn in Response to Male, But Not Female, Infant-Directed Speech.

Abstract: Previous research using a conditioned-attention paradigm demonstrated that 4-month-old infants of depressed mothers (a) failed to acquire associations when a segment of their mothers' infant-directed (ID) speech signaled the presentation of a smiling face but (b) did acquire associations when a segment of an unfamiliar nondepressed mother's ID speech signaled the face (P. S. Kaplan, J. -A. Bachorowski, M. J. Smoski, & W. J. Hudenko, 2002). In the present study, 5- to 13-month-old infants of depressed mothers f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
62
2
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 29 publications
(72 citation statements)
references
References 34 publications
6
62
2
2
Order By: Relevance
“…As was reviewed above, Kaplan et al (2004) showed that infants of chronically depressed mothers failed to learn in this paradigm in response to ID speech produced by their own depressed mother or an unfamiliar non-depressed mother, but showed better-than-normal learning in response to ID speech produced by an unfamiliar non-depressed father, relative to infants of non-depressed mothers. However, although they were obtained in tests with the infant's own, instead of an unfamiliar fathers', ID speech, the current findings showed that elevated depressive symptoms have similar adverse effects on the learning-promoting properties of fathers' as they do with mothers' ID speech.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As was reviewed above, Kaplan et al (2004) showed that infants of chronically depressed mothers failed to learn in this paradigm in response to ID speech produced by their own depressed mother or an unfamiliar non-depressed mother, but showed better-than-normal learning in response to ID speech produced by an unfamiliar non-depressed father, relative to infants of non-depressed mothers. However, although they were obtained in tests with the infant's own, instead of an unfamiliar fathers', ID speech, the current findings showed that elevated depressive symptoms have similar adverse effects on the learning-promoting properties of fathers' as they do with mothers' ID speech.…”
Section: Discussionmentioning
confidence: 99%
“…As was mentioned above, this was done to hold constant the procedure used in a prior study that had yielded evidence of significant voice-face associations (Kaplan et al, 2004;Exp. 2).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The rich input not only helps children to master morphologically and phonologically rich languages [2] but also provides the psychological comfort and stability [3]. However, little children in many countries lack necessary linguistic input due to the fact that parents either have no time to speak with their kids (that normally happens in the families with a high socio-economic status (henceforth -SES)), or do not correctly understand the importance of such communication (characteristics of the lower SES families).…”
Section: Introductionmentioning
confidence: 99%